(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Change of data into a digital organization with the appropriation of technology is called as digitization. By execution of digitalization, banks can give improved customer services. This gives accommodation to customers and helps in sparing time. Digitalization diminishes human mistake and in this way constructs customer dependability. Another flood of technology is altering the manner in which customers connect with their finances. From social to portable abilities, banks need to reconsider the manner in which they work together to convey a superior customer experience and stay aggressive. The ongoing presentation of open banking and the Payments Services Directive 2 (PSD2) guideline is hurrying this change by putting power in the hands of customers. Banks should now enable customers to share their financial data, for example, s pending propensities and standard payments, with approved outsider suppliers if customers wish to do as such. Furthermore, until the previous couple of years, banks were not picturing the colossal move in buyer behavior that happened because of the millennial age currently become the biggest consumers of financial products. With the expanding utilization of smart-telephones, digitization of banking part is unsurprising to get up to speed the expanding desires for the world. It in fact decreased human mistakes and expanded comfort. Presently, cyber dangers are on the ascent consequently, banks must be extremely watchful and ought to be set up to deal with cyber-attacks.